2021
DOI: 10.1016/j.heliyon.2021.e06866
|View full text |Cite
|
Sign up to set email alerts
|

Identification of PBMC-based molecular signature associational with COVID-19 disease severity

Abstract: The longevity of COVID-19 as a global pandemic, and the devastating effects it has had on certain subsets of individuals thus far has highlighted the importance of identifying blood-based biomarkers associated with disease severity. We employed computational and transcriptome analyses of publicly available datasets from PBMCs from 126 patients with COVID-19 admitted to ICU (n=50), COVID-19 not admitted to ICU (n=50), non-COVID-19 admitted to ICU (n=16) and non-COVID-19 not admitted to ICU (n=10), and utilized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 49 publications
3
19
0
Order By: Relevance
“…Differential expression of lncRNA in PBMC between severe and mildly affected COVID-19 patients has also been reported. It has been observed that increased level of LINC02207, LINC01127 was associated with the severe COVID-19 group, whereas LINC02084, LINC02446, LINC00861, LINC01871, and ANKRD44-AS1 were associated with the mild COVID-19 group [38]. PVT1 was downregulated in severe COVID-19 patients compared with non-severity [37].…”
Section: Altered Expression Of Lncrna In Sars-cov-2 Infected Cellsmentioning
confidence: 95%
See 2 more Smart Citations
“…Differential expression of lncRNA in PBMC between severe and mildly affected COVID-19 patients has also been reported. It has been observed that increased level of LINC02207, LINC01127 was associated with the severe COVID-19 group, whereas LINC02084, LINC02446, LINC00861, LINC01871, and ANKRD44-AS1 were associated with the mild COVID-19 group [38]. PVT1 was downregulated in severe COVID-19 patients compared with non-severity [37].…”
Section: Altered Expression Of Lncrna In Sars-cov-2 Infected Cellsmentioning
confidence: 95%
“…Expressions of hundreds of lncRNAs including uncharacterized novel transcripts have been identified in SARS-CoV-2 infected cells [32][33][34][35], BALF from the COVID-19 patients [35,36], and PBMC from COVID-19 patients [36][37][38][39]). In most of the studies, reanalyses of expression data for lncRNA from published transcriptomic data, except in two studies [33,37] were carried out.…”
Section: Altered Expression Of Lncrna In Sars-cov-2 Infected Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…LncRNAs have roles in viral transformation, viral latency maintenance, viral replication promotion, and viral-gene expression augmentation [ 96 ] ; implicate in modulating host cell immunity and/or inflammation, host cell energy/ metabolism, host cell cycle, and apoptosis; and thus negatively impact the normal physiological activities of host cells [ 97 ]. Multiple lncRNAs were differentially expressed during SARS-CoV-2 infection, which are considered potential disease biomarkers [ 98 ]. Metastasis-associated lung adenocarcinoma transcript 1 (MALAT1) and lncRNA X-inactive specific transcript (XIST) have been reported to play a key role during the SARS-CoV-2 inflammatory immune response [ 99 ].…”
Section: Hallmarks Of Sars-cov-2-mediated Neuropathologymentioning
confidence: 99%
“…Recent research has suggested that a unique non-coding RNA signature can aid in identifying the likelihood of developing specific disease outcomes [2]. Alterations of miRNA levels in the blood have been described in multiple inflammatory and infectious diseases, including SARS-related coronaviruses [3][4][5][6][7][8][9]. MiRNAs are endogenous small non-coding RNAs, around 22 nucleotides, that bind specific messenger RNAs (mRNAs) through complementary base-pairing [10].…”
Section: Introductionmentioning
confidence: 99%